PEDIATRIC MASTOCYTOSIS: AN UPDATE - Fiorina Giona (Mediterranean Journal of Hematology and Infectious Diseases)
Mastocytosis is a rare clonal disorder, characterized by excessive proliferation and accumulation of mast cells (MC) in various organs and tissues. Cutaneous mastocytosis (CM), the most common form in children, is defined when MC infiltration is limited to the skin. Systemic mastocytosis (SM), the most common form in adults, is characterized by MC proliferation and accumulation in organs, such as bone marrow, lymph nodes, liver and spleen (1). Genetic aberrations, mainly the KIT D816V mutation, play a crucial role in the pathogenesis of mastocytosis, resulting in enhancing MC survival and subsequent accumulation in organs and tissues (2,3). CM includes 3 forms: solitary mastocytoma, maculopapular cutaneous mastocytosis (MPCM) and diffuse cutaneous mastocytosis (DCM). In the majority of children with CM, skin lesions regress spontaneously around puberty; unfortunately, in a few cases, it is not a self-limiting disease (4). Even if SM occurs occasionally, all children with mastocytosis require planned follow-up over time. Children with mastocytosis often suffer from MC mediator-related symptoms, the most common of which is itching, often triggered by rubbing the lesions. Management of pediatric mastocytosis is mainly based on strict avoidance of triggers. Treatment with H1 and H2 histamine receptor blockers on demand, and the availability of epinephrine auto-injectors for the patients to use in case of severe anaphylactic reactions are recommended.